Agriculture Risk Financing in Southern Africa - World Bank (World Bank, Washington, DC, 2020)
This policy note is provided as an output under the World Bank’s Regional Advisory Service for Southern Africa, ‘Developing a Regional Risk Financing Framework for Agriculture and Food Security’. A key objective of this advisory service is to inform the public sector in Southern Africa on improvements to agriculture and food security risk financing policies and programs. The note is an output under component two of the project, which aims to identify agriculture risk financing policy options. The note aims to take stock of selected key financial risks affecting the agriculture sector in the Southern Africa Development Community (SADC) region and provide options to build financial resilience. Weather risks, price volatility, and pests and diseases are among the most important shocks affecting agricultural producers in the region, frequently with severe consequences for food security. This note gives (i) an overview of their regional impact in terms of economic and financial cost, as well as effects on food security; (ii) describes the status quo of use of agriculture risk financing instruments by countries in the region; and (iii) derives policy recommendations to further improve financial resilience to agricultural shocks using agriculture risk financing instruments. It should be noted that risk financing instruments are only one part of a comprehensive agriculture risk management approach. Other complementary agriculture risk management mechanisms and approaches, such as the development of commodity exchanges, agriculture trade policy, or warehouse receipt systems, are not the focus of this note.